2020
DOI: 10.7759/cureus.9226
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia Induced Headache: A Case Report and Literature Review

Abstract: A 51-year-old woman with a past medical history of migraine presented with severe headache for the last three weeks. The pain was intermittent and throbbing in nature. She has not experienced any headaches in the past several years. She took her migraine pills and over-thecounter analgesics, but the pain did not resolve. Initial evaluation including physical exam and neurological exam was normal. Her serum chemistry was unremarkable and CT scan of the brain was nonsignificant. The patient was diagnosed with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several studies have shown an association between migraine and trigeminal neuralgia. Trigeminal neuralgia is a localized peripheral neuropathy due to the irritation of the fifth cranial nerve (the trigeminal nerve) resulting in painful facial sensations, which is usually one-sided (Kataria et al, 2020). The association between migraine and trigeminal neuralgia remained significant in patients with migraine with aura, the mechanism of which is relatively unknown (Lin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an association between migraine and trigeminal neuralgia. Trigeminal neuralgia is a localized peripheral neuropathy due to the irritation of the fifth cranial nerve (the trigeminal nerve) resulting in painful facial sensations, which is usually one-sided (Kataria et al, 2020). The association between migraine and trigeminal neuralgia remained significant in patients with migraine with aura, the mechanism of which is relatively unknown (Lin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%